TRAFFIC NAVIGATOR - Mohamad Razi, Muhammad Muadz (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Traffic congestion had become a natural occurrence for the people in the 21st century. It had been accepted in modern life that the annoyance about it seems to fade as time goes by. High traffic congestion usually occurs during the peak hours on working days and the traffic can be so congested that drivers may get stuck in it for hours. The objective of this project is to develop an Android smart phone application that can assist drivers in Malaysia navigate through road traffic in its major cities. Through an Agile development method, the developer will gather information about Malaysia's major cities' road traffic and program the app using an Android Development Tool Kit and Google API's.